Career and job satisfaction of pre-primary teachers - POŠTEKOVÁ, Beáta (International Journal of Holistic Health, Sports and Recreation, 2023)
Promoting quality education depends on teacher job satisfaction. Student learning outcomes can improve when teachers are motivated, committed and dedicated to their work. This is more likely to happen when they are satisfied with their jobs. On the other hand, teachers who are not happy in their position may be more prone to burnout, which can have a negative impact on both their performance and student achievement. Helping children learn and develop is enjoyable for many instructors who choose to pursue this wonderful profession of teaching. One of the negative factors affecting teachers’ job satisfaction is the lack of appreciation of the teaching profession as a whole. As in any job, there are difficulties that can reduce job satisfaction. Workload, salary, work environment, and support from peers and management are some variables that can affect a teacher’s career and job satisfaction. Teachers should have access to professional development opportunities, resources and support, as well as a supportive work environment to promote job satisfaction and career success. Teachers may also benefit by seeking coaching or mentoring from more experienced instructors. In this paper, satisfaction with working conditions and motivation in the profession pre-primary teachers’ perceptions of satisfaction with working conditions and motivation in the profession are examined using a qualitative methodology through a questionnaire with 217 respondents.